2022
DOI: 10.3389/fendo.2021.807054
|View full text |Cite
|
Sign up to set email alerts
|

Hyperprolactinemia and Hypopituitarism in Acromegaly and Effect of Pituitary Surgery: Long-Term Follow-up on 529 Patients

Abstract: PurposeStudies on hyperprolactinemia and hypopituitarism in acromegaly are limited. We aimed to analyze the preoperative status, postoperative alterations, and correlated factors of hyperprolactinemia and hypopituitarism in acromegaly patients.MethodsThis is a single-center cohort study with long-term follow-up. We prospectively enrolled 529 acromegaly patients. Hyperprolactinemia and hypopituitarism were evaluated by testing hypothalamus-pituitary-end organ (HPEO) axes hormones before and after surgery.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 34 publications
(57 reference statements)
1
21
0
1
Order By: Relevance
“…Hypopituitarism (including central hypogonadism), reported in 10–80% of acromegalic cases, and hyperprolactinemia (affecting more than one third of the patients) are associated with a higher rate of subfertility/infertility in acromegalic patients when compared to a non-acromegalic population of the same age, in both females and males [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. Pituitary insufficiency and increased prolactin status are related to larger tumors; 90–95% of pituitary GH secreting tumors are macroadenomas; the additional negative role concerning fertility status is caused by secondary DM [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ].…”
Section: Sub/infertility Issues In Acromegalymentioning
confidence: 99%
See 1 more Smart Citation
“…Hypopituitarism (including central hypogonadism), reported in 10–80% of acromegalic cases, and hyperprolactinemia (affecting more than one third of the patients) are associated with a higher rate of subfertility/infertility in acromegalic patients when compared to a non-acromegalic population of the same age, in both females and males [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. Pituitary insufficiency and increased prolactin status are related to larger tumors; 90–95% of pituitary GH secreting tumors are macroadenomas; the additional negative role concerning fertility status is caused by secondary DM [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ].…”
Section: Sub/infertility Issues In Acromegalymentioning
confidence: 99%
“…Pituitary insufficiency and increased prolactin status are related to larger tumors; 90–95% of pituitary GH secreting tumors are macroadenomas; the additional negative role concerning fertility status is caused by secondary DM [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. For instance, one study from 2022 on 529 acromegalic individuals identified a rate of hyperprolactinemia of 39.1% and a prevalence of hypopituitarism of 34.8%, with the gonadal axis being the most affected pituitary axis; there was a hypogonadism frequency of 29.7% [ 45 ].…”
Section: Sub/infertility Issues In Acromegalymentioning
confidence: 99%
“…In the literature we collected, the incidence of preoperative adrenal Insu ciency was between 2.5% and 6.9%, hypothyroidism between 3.5% and 25.4%, hypogonadism between 10.2% and 51.1%, The incidence of Retention was between 0.1% and 30%. In contrast to new-onset pituitary dysfunction, existing preoperatively impaired pituitary function can be relieved by surgery [47]. However, in most cases, pituitary recovery is partial and requires continued hormone replacement therapy after surgery [48].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature we collected, the incidence of preoperative adrenal Insu ciency was between 2.5% and 6.9%, hypothyroidism between 3.5% and 25.4%, hypogonadism between 10.2% and 51.1%, The incidence of Retention was between 0.1% and 30%. In contrast to new-onset pituitary dysfunction, existing preoperatively impaired pituitary function can be relieved by surgery [47]. However, in most cases, pituitary recovery is partial and requires continued hormone replacement therapy after surgery [48].…”
Section: Discussionmentioning
confidence: 99%
“…At present, the main treatment is endoscopic transsphenoidal resection of tumors, but the biochemical remission rate after surgery is about 50-60% [4,5]. Although endoscopic transsphenoidal surgery has the advantages of visualization and minimal invasion, the surgery itself often has positive or negative effects on pituitary function, which is not only limited to the changes of growth hormone and IGF-1 but also includes thyroid, adrenal and gonadal axis hormones, which need drug substitution therapy [6]. Changes in pituitary hormone require clinicians to manage patients with long-term follow-up after surgical resection of the tumor, and choose radiotherapy and drug therapy if necessary.…”
Section: Introductionmentioning
confidence: 99%